Recruiting and developing the career path of professional marketing representatives in Iloilo City - Arreglado, Jhennilyn J.; Goyo, April Felvie; Madanguit, Marc Gretel R.; Maravillas, Jiahra Mae. (2009.)
Marketing of pharmaceutical conduces as a vital function in the health care delivery system. A lot of doctors, pharmacists and health care experts study about new medicine and about enduring research in the areas of their specialties, chiefly through effective and efficient interaction with professional marketing representatives. The job of a professional marketing representative is introducing new and promoting existing medicines to doctors and pharmacists. Also, a professional marketing representative discusses not only the clinical uses, dosages and uses of a certain drug but also channels both the doctors, pharmacists, other health care providers to their company's scientists and administrative staffs as the companies manufacture medicines which are really needed and also ensures the good quality of the medicines for the safety of the patients. This research paper is a modest effort or endeavor to find out the recruitment practices of pharmaceutical companies, the current status of the pharmaceutical industry, and the career development path of Pharmaceutical Marketing Representatives in Iloilo City. The findings of this study present data mainly about the different pharmaceutical companies. Second, the results reveal the legislations governing the industry and the level of growth of the pharmaceutical companies. Third, it shows the recruitment and career development practices of the said companies. Lastly, the study shows shows how to help in improving the human resource practices of pharmaceutical companies especially in hiring, selecting and giving advancement opportunities to their employees more specifically to the Professional Marketing Representatives. The study has been conducted through primary survey among the professional marketing representatives of the different pharmaceutical companies which involves 50 of them as respondents. The results of the survey and study show that there is a significant relationship between the recruitment practices and the career development path of the Professional marketing Representatives. There are 94% of the respondents said that they entered their current companies with an appropriate screening procedures like examinations and interviews. This illustrates that at the start of their career, there is already a competition between the aspirants of being a professional marketing representative. There are 94% of the respondents said that they entered their current companies with an appropriate screening procedures like examinations and interviews. This illustrates that at the start of their career, there is already a competition between the aspirants of being a professional marketing representative.
Research Paper ( BS Management). [Iloilo City : University of the Philippines Visayas - College of M]anagement,] -- March 21, 2003.